Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s12529-015-9466-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Symptoms Among Obstetric Fistula Patients Compared to Gynecology Outpatients in Tanzania

Abstract: Background Obstetric fistula is a childbirth injury prevalent in sub-Saharan Africa that causes uncontrollable leaking of urine and/or feces. Research has documented the social and psychological sequelae of obstetric fistula, including mental health dysfunction and social isolation. Purpose This cross-sectional study sought to quantify the psychological symptoms and social support in obstetric fistula patients, compared with a patient population of women without obstetric fistula. Methods Participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
51
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 45 publications
9
51
0
2
Order By: Relevance
“…Participants were drawn from a larger study investigating psychosocial sequelae of obstetric fistula [9]. Study inclusion criteria were 18 years of age or older, vesico-vaginal or recto-vaginal fistula from obstetric cause, and admission for surgical repair.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were drawn from a larger study investigating psychosocial sequelae of obstetric fistula [9]. Study inclusion criteria were 18 years of age or older, vesico-vaginal or recto-vaginal fistula from obstetric cause, and admission for surgical repair.…”
Section: Methodsmentioning
confidence: 99%
“…All study procedures were approved by institutional review boards at both collaborating institutions, and informed consent was obtained prior to data collection. For further information on this study's ethical clearance and consent process, see Wilson et al [9]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms of vaginal fistula include urine incontinence, faecal incontinence, foot drop, infertility, skin ulceration [2, 3] and depression [4, 5]. Often, the illness classic symptoms of faecal and urinary incontinence cause the participants to live socially isolated lives and psychological trauma besides losing their daily source of livelihoods.…”
Section: Introductionmentioning
confidence: 99%
“…About two thirds of a Tanzanian sample of women with fistulae reported social isolation due to their leaking (Bangser, et al, 2011), and studies in other settings observed fistula associated with divorce (Ahmed & Holtz, 2007), stigma (Yeakey, Chipeta, Taulo, & Tsui, 2009), depression (Balogun, 1994; Weston, et al, 2011), and general mental health dysfunction (Browning, et al, 2007; Goh, et al, 2005). Our own research has identified rates of depression and post-traumatic stress disorder among fistula patients that are significantly higher than women recruited from other gynecological clinics (Wilson, Sikkema, Watt, & Masenga, 2015). …”
Section: Introductionmentioning
confidence: 94%